Use of a recently developed thermal modulator within the context of comprehensive two‐dimensional gas chromatography combined with time‐of‐flight mass spectrometry: Gas flow optimization aspects. Issue 3 (11th December 2018) - Zoccali, Mariosimone; Giocastro, Barbara; Tranchida, Peter Q.; Mondello, Luigi
Abstract: The present research is based on the use of a recently developed comprehensive two‐dimensional gas chromatography thermal modulator, which is defined as solid‐state modulator. The transfer device was installed on top of a single gas chromatography oven, while benchtop low‐resolution time‐of‐flight mass spectrometry was used to monitor the compounds exiting the second analytical column. The solid‐state modulator was first described by Luong et al. in 2016, and it is a moving modulator that does not require heating and cooling gases to generate comprehensive two‐dimensional gas chromatography data. The accumulation and remobilization steps occur on a trapping capillary, this being subjected to thermoelectric cooling and micathermic heating. In this study, the effects of the gas linear velocity on the modulation performance were evaluated by using two different uncoated trapping capillaries, viz., 0.8 m × 0.25 mm id and 0.8 m × 0.20 mm id. Solid‐state modulator applications were carried out on a standard solution containing n ‐alkanes (C9, C10, C12 ), and on a sample of diesel fuel. The results indicated that the type of trapping capillary and gas velocity have a profound effect on modulation efficiency.